Investigation of the Effect of Addition Nano-papyrus Cane on the Mechanical Properties of Concrete - Faisal K. Abdulhussein; Zahraa F. Jawad; Qais J. Frayah; ِAwham J. Salman (Salehan Institute of Higher Education, 2021)
This paper investigates the effect of nano-papyrus cane ash as an additive on concretes’ mechanical and physical properties. Three types of concrete mixtures, 1:2:4, 1:1.5:3, and 1:1:2 were prepared for each mixture, nano-papyrus ash was added in five different dosages of 0.75, 1.5, 3, 4.5, and 6% by weight of cement; therefore, eighteen mixes would be studied in this work. Physical properties represented by dry density and slump were also measured for each mix. Moreover, to evaluate the mechanical properties development split tensile strength and compressive strength were obtained at age (7 and 28). Results manifested that the adding of nano ash developed the compressive strength and split tensile strength of concrete and the maximum enhancement recognized in the mixes with a content of 4.5% nano-papyrus in each studied mixture in this work. The slump test results indicated that the workability of concrete increased with adding nano-papyrus ash gradually with increasing nanoparticles' content. As well as, dry density was significant increased with nano-papyrus ratio; greater values were recorded in mixtures with 1.5-4.5% content of nano-papyrus. When comparing the concrete mixes used, it was found that the best results were obtained with 1:1:2 mixtures. This remarkable improvement in concrete properties considers the nano-papyrus is considered a cement economical and useful replacement for traditional construction material. Doi: 10.28991/cej-2021-03091649 Full Text: PDF